Antibiotic coating of the artificial urinary sphincter (AMS 800): is it worthwhile? - Hüsch, Tanja; Nyarangi-Dix, Joanne (Urology, 2017)
Objective: To investigate the impact of the antibiotic coating InhibiZone on the infection and explantation rates of the AMS 800 in comparison to the AMS 800 without InhibiZone. Materials and Methods: We retrospectively identified 305 patients with an AMS 800 in a multicenter cohort study. Patients were subsequently divided into InhibiZone and without InhibiZone-coated groups. Infection and explantation rates were analyzed by univariate and consecutively by multivariate logistic regression adjusted to variable risk factors. The infection-free interval was estimated by Kaplan-Meier plot and compared by the log-rank test. A P value below .05 was considered statistically significant. Results: We identified 47 patients with InhibiZone and 258 without InhibiZone coating. In univariate analysis, we could not identify a significant difference in infection (P = .932) or explantation (P = .715) rates between the groups. In multivariate analysis, impaired wound healing (P = .008) and urethral erosion (P < .001) were independent predictors for infection. The InhibiZone coating neither demonstrated significant influence on the infection rate (P = .534) nor on the explantation rate (P = .214). There was no significant difference in estimated infection-free survival between the groups (P = .265). Conclusion: The antibiotic coating of the AMS 800 had no significant impact on infection or explantation rates in our cohort.